Audience perception of code. Issue 2 (2nd July 2016) - zmölnig, IOhannes m.
ABSTRACT: By projecting the screen of the live coding performer, the audience is made a promise: to gain insight into what is happening on stage. However, in a typical concert situation most spectators will not be intimate with the programming language in use by the performer. Whether an audience is willing to follow the presented code to a detailed level where they are able to map the read text to the musical structure they perceive, remains debateable. Text as a medium always implies that the onlooker should read it. As soon as a text is identified as such it wants to be understood. If the onlooker is not able to perform the reading, they might become frustrated and turn away from the text. If the content is not decipherable, the text becomes an empty symbol, devoid of a primary meaning. Within the author's approach to this problem, a multi-layered representation of code is provided, so the audience may choose from several readings of the text simultaneously, picking those they feel comfortable with.